Internalization of Religious Moderation Values in Islamic Religious Education: A Multisite Study at SMAN 1 and SMKN 1 Garut - Ade Saepuloh; Mahmud Manan; Muslihun Muslihun (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to examine the forms and causes of radicalism, elaborate on the concept and practice of internalizing religious moderation values in Islamic Religious Education (PAI) learning, and assess the effectiveness and challenges of this process in building students’ ideological resilience. The research adopts a qualitative approach with a multisite study design at SMAN 1 and SMKN 1 Garut. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive data analysis model. The findings indicate that radicalism among students in Garut develops latently and symbolically through exclusivism, ideological segregation, and exposure to intolerant narratives in digital media and non-formal environments, influenced by psychosocial, historical, economic, and cultural factors. Religious moderation values have been contextually and culturally internalized at SMAN 1 and SMKN 1 Garut through PAI learning, school culture, as well as interfaith and anti-violence programs, making both schools resilient models against radicalism. The internalization process proceeds through three structured stages: transformation, transaction, and transinternalization, with dialogical and reflective approaches that encourage students to internalize and practice values of tolerance and anti-radicalism in their daily lives. The success of this internalization is influenced by participatory learning approaches and supportive environments; however, challenges remain in the form of ideological enclaves and external influences that do not support moderation.